Nilai-Nilai Kearifan Lokal Dalam Kebudayaan Tari Andun Di Daerah Bengkulu Selatan - Fitriana, Aziza Fajar; Iqbal, Moch (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2025)
The purpose of this study is to provide an overview of the Andun dance of the Serawai tribe and the values ​​of community love in that culture. The research method used is literature review using the opinions of experts and previous research. Andun dance is a traditional dance that lives, grows and develops in society. From the past until now it is not known who created it and what year this dance was first danced. People only say that this dance has always existed. Andun dance is a dance that can provide entertainment and directing the audience through the dance performed in the performance, the results of this study indicate that the Andun dance has the values ​​of people's love in the Andun dance culture which shows that it means life in a household. This Andun dance has a deep meaning for the people of Serawai, so the value -The values ​​contained in the Andun dance performance are very noble, including the values ​​of decency, religion, society, ethics and aesthetics. This is not only entertainment that reflects the performance of this traditional dance, but also shows the form of decency and courtesy of the people of Serawai. This is proven because the dancers, both women and men, must follow the rules and regulations in performing this traditional dance. The dance is mutually agreed upon.